Pozycja konkurencyjna spółek giełdowych kontrolowanych przez inwestorów zagranicznych - Wypych, Mirosław (Foreign-controlled Stock Exchange Enterprises' Competitive Position, 2007)
The target of the paper is opinion about competitive position of foreign-controlled stock exchange enterprises. The author presents rating rules for competitive position and foreign investors' strategies referring to controlled enterprises. The empirical part contains an analysis of companies being present at the Warsaw Stock Exchange during the years 2003-2005. The paper shows that the competitive position of strategic investor-controlled companies is stronger than the others.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 468-475